Economic growth dynamics in Kupang City: The role of poverty, human development index, and inflation - Dima, Enike Tje Yustin; Nalle, Frederic Winston (Goodwood Publishing, 2025)
Purpose: This study analyzes the impact of poverty, the Human Development Index (HDI), and inflation on economic growth in Kupang City from 2014 to 2023. Method: This study applies a quantitative method using multiple linear regression. Secondary data were obtained from the Central Bureau of Statistics (BPS) of Kupang City. Data analysis was performed using SPSS version 29.00 to examine the relationships between the variables. Results: Simultaneous poverty, HDI, and inflation have a significant effect on economic growth. However, poverty has a partially negative but insignificant effect, indicating that structural issues, such as access to resources, income inequality, and informal sector dynamics, also shape regional economic performance. HDI has a negative and significant impact, suggesting that improvements in education and health are not yet fully aligned with labor market absorption. Inflation has a positive but statistically insignificant effect, implying that short-term price movements do not directly determine growth in Kupang. Conclusions: Inclusive and integrated economic strategies are essential for achieving sustainable growth in Kupang City. Limitations: This study is limited by its use of secondary data and a purely quantitative approach, which may not capture institutional or behavioral nuances. Future studies should consider mixed methods to obtain more comprehensive insights. Contribution: This study provides empirical evidence to support regional development policies focused on poverty alleviation, better alignment of human capital with economic needs, and inflation management.